2017
DOI: 10.1002/ana.24954
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neurofilament light: A biomarker of neuronal damage in multiple sclerosis

Abstract: ObjectiveNeurofilament light chains (NfL) are unique to neuronal cells, are shed to the cerebrospinal fluid (CSF), and are detectable at low concentrations in peripheral blood. Various diseases causing neuronal damage have resulted in elevated CSF concentrations. We explored the value of an ultrasensitive single‐molecule array (Simoa) serum NfL (sNfL) assay in multiple sclerosis (MS).MethodssNfL levels were measured in healthy controls (HC, n = 254) and two independent MS cohorts: (1) cross‐sectional with pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

78
1,069
14
21

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 863 publications
(1,222 citation statements)
references
References 52 publications
78
1,069
14
21
Order By: Relevance
“…In a cohort of 42 MS patients followed in a trial of riluzole over 24 months which included MS patients with high disability scores, serum NfL levels were correlated with EDSS change ( P = 0.009)15. In a study following subjects for a mean of 3.1 years, serum NfL levels were associated with EDSS assessments (beta = 1.105, P < 0.001) 13. As discussed above, NfL increases are closely correlated with new T2 lesions, and thus the short‐term correlations may reflect the effect of relapses and new lesion formation, which has limited impact on longer term outcomes.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In a cohort of 42 MS patients followed in a trial of riluzole over 24 months which included MS patients with high disability scores, serum NfL levels were correlated with EDSS change ( P = 0.009)15. In a study following subjects for a mean of 3.1 years, serum NfL levels were associated with EDSS assessments (beta = 1.105, P < 0.001) 13. As discussed above, NfL increases are closely correlated with new T2 lesions, and thus the short‐term correlations may reflect the effect of relapses and new lesion formation, which has limited impact on longer term outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Shorter term studies have found correlations between new gadolinium‐enhancing lesions and serum NfL values 13, 15, 31. Patients with either brain, spinal, or both brain and spinal gadolinium‐enhancing lesions had higher serum NfL than those without 13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has now changed with the introduction of a highly sensitive single molecule array (Simoa) technology, 5 allowing reliable detection of blood NfL levels. 6 Several studies have proven that NfL in CSF and serum are very well correlated to each other, supporting the notion that serum NfL may be used as a bloodderived marker for neuro-axonal damage. [7][8][9] There is evidence showing that both CSF and serum Nfs levels are associated with disease activity, physical disability, and magnetic resonance imaging (MRI) changes in MS; however, clinical follow-up time was relatively short in most of these studies.…”
mentioning
confidence: 71%